PENGARUH WARNA TERHADAP INGATAN JANGKA PENDEK (SHORT TERM MEMORY) - Sri Ayu Mutmainah Kurniawati; Hurun Inun Fathun Buka; Intan Nur'ain Akuba; Sinderella Utina; Najmah Dwi Susilowati; Rezaldi Putra Maunu (program studi psikologi, 2023)
Short term memory is the process of storing information in memory for a temporary period of time. Color serves as a powerful information channel for the human cognitive system and has a significant role in improving memory work. This study aims to examine the effect of color use on short-term memory ability in psychology students. This study involved two groups of participants, namely the experimental group who were given colored animal images (chromatic) and the control group who were given black-and-white images (achromatic). Data was collected through pre-test and post-test to measure the amount of information that could be remembered by the participants. Normality test using Shapiro-Wilk showed that the pre-test data of the experimental and control groups were normally distributed, while the post-test data of the control group were not normally distributed. Therefore, the Wilcoxon Signed Ranks Test was used for data analysis. The results of the analysis showed that the experimental group that was given colored pictures showed a significant improvement in recall (Asymp. Sig. = 0.018), while the control group showed no significant difference between the pre-test and post-test (Asymp. Sig. = 0.182). These results indicate that the use of color has a positive effect on short-term memory ability. This study contributes to the understanding of how color can be used to improve memory, with practical implications in the design of more effective learning materials and learning spaces.